Consumer behaviour : a European perspective - Antonides, Gerrit, 1951-; Raaij, W. Fred van. (New York : John Wiley and Sons, 1998)
This book is about: Macro-factors in consumption; Basic processes; Social processes; After-sales processes; Applications.
Keywords: Marketing; Economics; Consumer; Consumer behavior -- Europe; Consumption (Economics) -- Europe; Marketing research -- Europe